Building Blocks of Upward Planar Digraphs - Healy, Patrick; Lynch, Karol (Journal of Graph Algorithms and Applications, 2007)
The upward planarity testing problem consists of testing if a digraph admits a drawing Γ such that all edges in Γ are monotonically increasing in the vertical direction and no edges in Γ cross. In this paper we reduce the problem of testing a digraph for upward planarity to the problem of testing if its blocks admit upward planar drawings with certain properties. We also show how to test if a block of a digraph admits an upward planar drawing with the aforementioned properties. <!—->